The problems of philosophical ontology from an analytic perspective - Shramko, Yaroslav (Actual Problems of Mind, 2018)
This is a review paper devoted to the specific features of an examination in analytic philosophy of some classical ontological problems. In particular, the problems of being, identity, substance, universals, and causality are under consideration. It is stressed that analytic philosophy not only precises and clarifies the formulations and the very statement of the problems, but proposes also a new view of these and other issues and some new solutions for them. In the focus of attention there are certain conceptions developed by Gottlob Frege, Bertrand Russell, David Lewis, Edward Lowe and some others. Analytic philosophy is characterized by its commitment to the clarity and preciseness of the problem setting and the notions defined, as well as by an extensive use of the heuristic methodology of the language analysis and the possibilities of the modern logic.